Centronics parallel port interface (II) - Alvarez, Hans Christian M. (1999)
A standard interface for items of test and instrumentation in electronics laboratories that will enable directly printing observable waveforms in an oscilloscope without the use of a PC is a very helpful tool in the process of experimentation and documentation. By accessing the IEEE Bus found on most measuring instruments, data from these instruments can now be accessed. The Intel Microprocessors Laboratory sought to develop a converter that will reconcile the IEEE Bus standard with the protocol for the parallel printer port, enabling the channeling of data from the oscilloscope to the printer. Unfortunately, the first version of the project was not fully bug-free. The output of the printer contained several unwanted characters - characters that were not supposed to be there. The objective of the project is to debug the first version of the 'Centronics Parallel Port Interface' and design a new board that will be able to print an error-free hardcopy of the displayed waveforms in an oscilloscope. The implementation of the project will be done using Field Programmable Gate Arrays (FPGA), a type of an Application Specific IC (ASIC). This new version of the Centronics Parallel Port Interface successfully achieved the objectives set. After testing and debugging of the original project design, timing errors proved to be the main cause of the errors. A new board was designed and an error-free hardcopy of waveforms displayed in an oscilloscope can now be easily obtained.
Thesis (B.S. Electronics and Communications Engineering)--University of the Philippines, Diliman.
Keywords: Ports (Electronic computer system); Microcomputers -- Programmable peripheral interfaces; Centronics parallel port interface; Parallel port interface